Spiritual Caring Behavior Tool Development - Sanglar Polnok; MA. Elizabeth C. Baua (Humanistic Network for Science and Technology (HNST), 2019)
The study’s aim was to explore Thai Buddhist nurses manifest spiritual caring behaviors based on cultural practices, values & beliefs of Buddhism, then a spiritual caring behavior tool for nurses was developed. Exploratory-sequential mixed methods design was utilized using Phenomenology. Ten informants were selected The results yielded three major themes, namely: Focus on the Nurse-Patient Caring Relationship with two subthemes which are Responsibility to Reach out and Engagement. The second theme is Presence of Being in a Caring Moment under which are two subthemes which are Caring based on Patients’ Needs and Context and Praise on Self Dignity and Human Rights. The third theme is Engagement in “Active Caring and Healing” with two subthemes whick are Allow Another to be an “Active Self-Healer/Carer” and Autonomy for Decision Making. The developed tool underwent forward and backward translation from Thai to English. The initial SCBT consisted of 26 items with I-CVI 0.80-1.00 and S-CVI 0.95. Exploratory Factor Analysis was utilized to find two factors, which are Proper Environment and Autonomy in Making Decision.The revised-spiritual caring behavior tool has only 25 items. The SCB tool was found to be a reliable tool with a Cronbach’s Alpha coefficient (13 items) of 0.927 (part 1) and (12 items) 0.94 (part 2). Keywords: beliefs; cultural practices; spirituality; spiritual care; spiritual caring behavior tool; values